Diversity and dynamics of microbial communities at each step of treatment plant for potable water generation - Lin, W; Yu, Z; Zhang, H; Thompson, I (Elsevier, 2013)
The dynamics of bacterial and eukaryotic community associated with each step of a water purification plant in China was investigated using 454 pyrosequencing and qPCR based approaches. Analysis of pyrosequencing revealed that a high degree diversity of bacterial and eukaryotic communities is present in the drinking water treatment process before sand filtration. In addition, the microbial compositions of the biofilm in the sand filters and those of the water of the putatively clear tanks were distinct, suggesting that sand filtration and chlorination treatments played primary roles in removing exposed microbial communities. Potential pathogens including Acinetobacter, Clostridium, Legionella, and Mycobacterium, co-occurred with protozoa such as Rhizopoda (Hartmannellidae), and fungi such as Penicillium and Aspergillus. Furthermore, this study supported the ideas based on molecular level that biofilm communities were different from those in corresponding water samples, and that the concentrations of Mycobacterium spp., Legionella spp., and Naegleria spp. in the water samples declined with each step of the water treatment process by qPCR. Overall, this study provides the first detailed evaluation of bacterial and eukaryotic diversity at each step of an individual potable water treatment process located in China. © 2013 Elsevier Ltd.